Emergence of carbapenem-resistant Klebsiella spp. infections in a Turkish university hospital: epidemiology and risk factors - Murat Dizbay; Ozlem Guzel Tunccan; Omer Karasahin; Firdevs Aktas (Journal of Infection in Developing Countries)
Introduction:Risk factors for nosocomial carbapenem-resistant Klebsiella spp. (CRK) infections were analyzed in this study.